A COMPARISON OF SPONGE FAUNA OF EXPOSED AND SHELTERED REEF FLATS IN EASTERN INDONESIA - Amir, Ichsan (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1992)
A total of 116 specimens belonging to 61 sponge species were colleted from the reef flat of four different localities in Eastern Indonesia, namely : Maisel, east of Sumba, north of Sumbawa and^ Bahuluang. The sponge species of exposed (Maisel), disturbed (Sumba and Sumbawa) and sheltered (Bahuluang) reef flats are compared using cluster and inverse analysis. The differences in composition of sponge species among those localities are described and discussed.